1983
DOI: 10.1523/jneurosci.03-01-00053.1983
|View full text |Cite
|
Sign up to set email alerts
|

An antiserum against the PC12 cell line defines cell surface antigens specific for neurons and Schwann cells

Abstract: Antibodies raised in rabbits and in guinea pigs against nerve growth factor-treated PC12 cells were absorbed exhaustively with three non-neuronal cell lines. In immunofluorescent staining experiments, these absorbed sera, designated anti-PC12, labeled specifically several different types of cultured neurons, including cerebral, cerebellar, spinal, dorsal root, and superior cervical neurons. Non-neuronal cells in these cultures, such as astrocytes, oligodendrocytes, and fibroblasts, were not labeled. However, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 33 publications
(50 reference statements)
5
43
0
Order By: Relevance
“…(4) Finally, proteins shed from the cell surface are released as a singlemolecular-weight species and are not found in the culture medium as a series of lower molecular weight peptides. This is true for fibroblast proteins (see, for example, McCormick et al, 1979) as well as for surface proteins of nerve and glial cells (RichterLandsberg et al, 1984;Stallcup et al, 1983;Sweadner, 1983). The inclusion of the protease inhibitor Kallikrein in the culture medium had no effect upon the pattern of extracellular protein synthesis (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) Finally, proteins shed from the cell surface are released as a singlemolecular-weight species and are not found in the culture medium as a series of lower molecular weight peptides. This is true for fibroblast proteins (see, for example, McCormick et al, 1979) as well as for surface proteins of nerve and glial cells (RichterLandsberg et al, 1984;Stallcup et al, 1983;Sweadner, 1983). The inclusion of the protease inhibitor Kallikrein in the culture medium had no effect upon the pattern of extracellular protein synthesis (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…The major criterion on which the classification of the nerve and glial cells was made was electrical excitability, but a large number of other markers, such as cell-surface antigens, are in agreement with the physiology. Nile and Nl are nerve-specific antigens (Richter-Landsberg et al, 1984;Stallcup, 198 1;Stallcup et al, 1983), and G2 is found only on some glial cells (Stallcup and Cohn, 1976). The clonal mesoderma1 cell lines were derived from both normal embryonic and neoplastic cells.…”
Section: Cell Linesmentioning
confidence: 99%
“…Binding of anti-NILE, anti-N-CAM, tetanus toxin, and antibody to glial fibrillary acidic protein to cells in primary culture was detected by immunofluorescence as described previously (5,13). For experiments in which neurite outgrowth or fasciculation was to be quantitated, control cultures or cultures that had been incubated in the presence of tetanus toxin, anti-NILE or anti-N-CAM were stained by using sequential 30-min incubations with tetanus toxin, rabbit antitoxin, and fluorescein-labeled goat antibody against rabbit immunoglobulin.…”
Section: Methodsmentioning
confidence: 99%
“…Closely related glycoproteins have now been found on the surfaces of all neuronal cell lines examined and all neurons in primary culture, including neurons of central, sensory, and sympathetic origin (4-7). Schwann cells also express a NILE-related component (5,6). Although they are immunologically cross-reactive, these neuronal glycoproteins are not identical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation